Poststroke Anxiety at 1 Year After Rehabilitation: A Multicenter Study. Issue 1 (January 2022) - Kuptniratsaikul, Vilai; Bun-in, Jiraporn; Limampai, Patchara; Pooliam, Julaporn
Abstract : Poststroke anxiety affects rehabilitation outcomes. This study aimed to investigate the prevalence of and factors associated with anxiety among patients with stroke at the 1 year after rehabilitation from 9 tertiary centers. Anxiety, functional score, and quality of life were evaluated by the Hospital Anxiety and Depression Scale-anxiety subscale (HADS-A), modified Barthel Index, and World Health Organization Quality of Life-BREF (WHOQoL-BREF), respectively. This study reveals 20 (11.7%) patients with stroke who developed anxiety, and 18 from 171 patients (10.5%) were new cases of anxiety, which was more than double the rate at discharge (4.7%). Factors related to anxiety were depression (adjusted odds ratio [aOR]: 30.7) and having complications (aOR: 12.48).